2023
DOI: 10.1021/acs.jpca.3c00332
|View full text |Cite
|
Sign up to set email alerts
|

Semi-microscopic Theory for the Current Rectification Phenomenon in Nanogap Molecular Devices

Abstract: A semi-microscopic theory is developed for heterogeneous electron transfer (HET) kinetics based on the energy level alignment approach at self-assembled monolayer (SAM) covered metal electrodes. Theory provides the electronic and molecular property-dependent equations for the HET rate constant (k 0) and the transfer coefficient (α) for potential. k 0 is formulated using the activation free energy as a product of the SAM covered metal work function (WF) and fractional electronic charge exchanged at the transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The effective applied potential at X ‡ is characterized through the transfer coefficient (α) or screening factor for the applied potential in eq of ET kinetics. Earlier we showed that for the nanogap molecular device, the transfer coefficient depends on the reaction coordinate at the transition state and a characteristic electronic-dipolar coupling length l e d . Using X ‡ = (2 l TF + r i )/2 in potential drop factor, we obtain a special case without spacer in nanogap molecular device for the transfer coefficient as α = exp ( X l e d ) exp ( l T F + r i / 2 l e d ) The potential drop or screening factor in eq is useful to formulate the applied potential dependent reaction current and exchange current in HET.…”
Section: Conceptual Formalismmentioning
confidence: 99%
See 3 more Smart Citations
“…The effective applied potential at X ‡ is characterized through the transfer coefficient (α) or screening factor for the applied potential in eq of ET kinetics. Earlier we showed that for the nanogap molecular device, the transfer coefficient depends on the reaction coordinate at the transition state and a characteristic electronic-dipolar coupling length l e d . Using X ‡ = (2 l TF + r i )/2 in potential drop factor, we obtain a special case without spacer in nanogap molecular device for the transfer coefficient as α = exp ( X l e d ) exp ( l T F + r i / 2 l e d ) The potential drop or screening factor in eq is useful to formulate the applied potential dependent reaction current and exchange current in HET.…”
Section: Conceptual Formalismmentioning
confidence: 99%
“…Earlier we showed that for the nanogap molecular device, the transfer coefficient depends on the reaction coordinate at the transition state and a characteristic electronic-dipolar coupling length l e d . Using X ‡ = (2 l TF + r i )/2 in potential drop factor, we obtain a special case without spacer in nanogap molecular device for the transfer coefficient as α = exp ( X l e d ) exp ( l T F + r i / 2 l e d ) The potential drop or screening factor in eq is useful to formulate the applied potential dependent reaction current and exchange current in HET. The operative potential at the transition state has a reduced value depending on the solvent dipole size ( r d ) and the separation of electroactive groups from the metal jellium surface.…”
Section: Conceptual Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Tao J. team reduced the HOMO to -5.3 eV and the LUMO to -2.8 eV in 1,6-DTEP of OPDs cuts the dark current and heightens sensitivity beyond 10 6 A/W [20][21][22]. An optimal bandgap of the electroactive groups is vital for superior OPD performance, broader spectral response, and improved photocurrent and responsivity [23]. Overall, accurately tuning HOMO and LUMO not only boosts the performance of these organic optoelectronic devices but also broadens their application scope, which is key to high-performance organic optoelectronic devices and propels the advancement of organic materials in optoelectronics.…”
Section: Introductionmentioning
confidence: 99%